Are high-performance work systems (HPWS) appreciated by everyone? The role of management position and gender on the relationship between HPWS and affective commitment. Issue 5 (24th July 2019) - Andersén, Jim; Andersén, Annelie
Abstract : Purpose: Although most studies on HPWS focus on various firm-level outcomes, there has been an increasing interest in how employees are affected by HPWS. However, most of these studies use social exchange theory and, based on an idea of reciprocal exchange, implicitly assume that all employees become more affectively committed to organizations using HPWS. Based on social identity theory, the authors argue that management position and gender likely influence how individuals respond to HPWS. Thus, the purpose of this paper is to examine how HPWS affects AC among managers, subordinates, men and women. Design/methodology/approach: Hierarchical linear model analysis of 356 employees in 26 Swedish small- and medium-sized manufacturing companies. Findings: In the sample examined, managers and women show increased affective commitment (AC) in organizations using HPWS. For men with non-managerial positions, the results indicate a reversed relationship, i.e. HPWS could actually reduce AC. Originality/value: The findings indicate the need to consider individual differences when examining the effect of HPWS, and highlight the usefulness of relational-oriented theories when studying the employee outcomes of HRM-systems.